359 Prevalence and predictors of psychological distress at 12 years post-injury. (20th November 2022) - Owen, Helen; Wyeth, Emma; Samaranayaka, Ari; Derrett, Sarah
Abstract : Background: Injuries have detrimental impacts on mental health, even after physical recovery. In our Prospective Outcomes of Injury Study (POIS), 25% of participants, with a range of injury severities, experienced psychological distress three months post-injury; declining to 16% by 24 months. Internationally, studies of hospitalised patients found distress persisted beyond 24 months post-injury and remained higher than in the general population. This study aims to describe the prevalence of psychological distress 12 years post-injury, and investigate pre-injury and injury-related characteristics associated with long-term distress. Methods: POIS recruited 2856 New Zealanders injured between 2007 and 2009. Now, 12-years post-injury a further interview has been completed. The Kessler Psychological Distress Scale (K6) was used to measure psychological distress outcomes. Data about a range of pre-injury and injury-related characteristics have previously been collected via earlier interviews or electronic injury-related data (e.g., hospitalisations, NISS). Results: Twelve years post-injury, 1543 people were re-interviewed (75% of eligible people); 12% reported psychological distress. Univariable analyses found socio-demographic factors (e.g., being older, education) were associated with reduced risk of psychological distress. Other pre-injury (e.g., inadequate income, mental/physical comorbidities) and post-injury factors (e.g., distress at 3-months) were associated with increased risk. Multivariable models are currently being developed. Conclusion: Clinically relevant distress persists long-term post-injury among adults with varying injury severities, types, and causes, and at higher prevalence than in the general population (7.9%). Learning Outcomes: Early identification of injured individuals at risk of long-term psychological distress indicates opportunities for timely interventions to improve outcomes.